Cyber Sovereignty and Artificial Intelligence Regulation in Indonesia as A Strategy for Strengthening Legal Frameworks and Public Protection - Abdi, Shafa Sakinah; Pratiwi, Pingki (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The rapid development of artificial intelligence (AI) in Indonesia has brought significant transformations in the economic, communication, and public service sectors, while also giving rise to the potential for cybercrimes, such as digital fraud, identity manipulation, and the spread of false content. This phenomenon underscores the urgency of establishing a comprehensive legal framework to close regulatory loopholes that have the potential to threaten legal certainty, accountability, and human rights protection.Purposes of the Research: This study aims to analyze the urgency and regulatory strategy of AI in Indonesia through an integrated approach that includes regulatory structure, legal substance, and legal system based on the principle of cyber sovereignty.Methods of the Research: The research uses a normative juridical method by examining primary legal materials, such as national laws and regulations and relevant international legal instruments, as well as secondary legal materials in the form of literature, journals, and opinions of legal experts.Findings of the Research: Through an integrated approach that includes regulatory structures, legal substances, and legal systems based on the principle of cyber sovereignty, it is found that Indonesia needs adaptive, comprehensive, and sustainable AI regulations to ensure human rights protection, digital security, and responsible use of technology.